Insect Hymnenopteran Parasitoids of Sugarcane Pest and Role As Biological Control Agents - Bhupinderjit Kaur Heer; Veerpal Kaur (International Journal of Insects, 2024)
The present study is short communication of insect parasitoids belongs to order Hymenoptera. Sugarcane crop attract number of insect pests that flourish on it, and cause about 15- 20% yield loss and minimize the productivity, this reduction in yield increase when the insect parasitoids attack on pest. There are some major parasitoids Orders that attack on the number of crops pest, like Dipteran, Lepidopterans, Neuropteran etc. and one of the major Order is Hymenopteran. As the agriculture field is growing day by day, number of methods are invented to deal with these pests, biological control is one of the best methods. In biological control methods, parasitoids are used to kill the insect pest under the controlled conditions and temperature as they infiltrate the physiology of insect pest to ensure their own survival. Biological control help to reduce the use of pesticides and other chemicals that kill that not only kills insect pest but also leaves the harmful effect on the environment. But the use of parasitoids in biological control programs requires careful consideration of factors like host specificity, environmental impact and potential interaction with other organisms. Some of the parasitoids of sugarcane pest are Cotesia flavipes, Trichogramma spp., Telenomus remus, T. chilonis etc. Parasitoids provide food source to other animals thereby supporting food chain. But activities like deforestation, urbanization, changes in temperature and precipitation, presence of invasive species can destroy the habitat of parasitoids, affect parasitoid populations and interactions and can disrupt parasitoid-host relationships and ecosystems
Keywords: Hymenopteran; Parasitoids; ecosystems; insect pest; sugarcane